Pendampingan Penguatan Tertib Administrasi dan Tata Kelola Keuangan untuk Meningkatkan Akuntabilitas Pengelolaan Yayasan Ukhuwah Insaniyah - Hartini Prasetyaning Pawestri; Untung Wahyudi; Survival Survival; Mulyono Mulyono; Inayatus Sholihah (Lembaga Pengembangan Kinerja Dosen, 2026)
Non-profit foundations are required to implement transparent and accountable administrative and financial governance to strengthen stakeholder trust and organizational sustainability. However, Yayasan Ukhuwah Insaniyah in Malang City faced several challenges, including manual administrative procedures, unstructured document archiving, and non-standardized financial recording practices. This community service program aimed to strengthen administrative and financial governance by improving the management capacity of the foundation to enhance organizational accountability. The program used a participatory approach through observation, focus group discussions, training, mentoring, and learning-by-doing activities. The implementation involved four stages: preparation, mentoring, implementation, and evaluation with sustainability planning. The results showed improvements in administrative management through standardized incoming and outgoing mail procedures, systematic document archiving, standardized financial recording formats, and enhanced financial reporting practices. Furthermore, the program increased management awareness of transparency, accountability, and good governance principles. The participatory mentoring approach encouraged collaboration, strengthened institutional capacity, and supported sustainable organizational transformation. These findings indicate that combining capacity building with administrative and financial governance improvement is an effective strategy for enhancing accountability, service quality, and public trust in non-profit foundation management.